If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 2 + x = 5x + 5 Reorder the terms: 2 + 3x + x = 5x + 5 Combine like terms: 3x + x = 4x 2 + 4x = 5x + 5 Reorder the terms: 2 + 4x = 5 + 5x Solving 2 + 4x = 5 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. 2 + 4x + -5x = 5 + 5x + -5x Combine like terms: 4x + -5x = -1x 2 + -1x = 5 + 5x + -5x Combine like terms: 5x + -5x = 0 2 + -1x = 5 + 0 2 + -1x = 5 Add '-2' to each side of the equation. 2 + -2 + -1x = 5 + -2 Combine like terms: 2 + -2 = 0 0 + -1x = 5 + -2 -1x = 5 + -2 Combine like terms: 5 + -2 = 3 -1x = 3 Divide each side by '-1'. x = -3 Simplifying x = -3
| .66x+4=.6-2 | | 230+.15x=369.50 | | 2x+57=5x | | 3a+1=3.6(1a-1) | | 5+3h=4h | | x-(1-2x)= | | -7-5n=28 | | 32+4(c-1)=(4c+5) | | 9x^2-10.5x-73.5=0 | | 9t+20=19t-6t-20 | | 28-0.3y=0.7y | | 7(r-7)=-49 | | 7(7x+9)=49x-10 | | -6x+6x+14=14 | | 9m-14= | | x*.10=x*.15 | | 14-3n=26 | | 8c+5(c-3)= | | x^3-3x^2+9x-27=0 | | 5x-30=40+3x | | 2x+7=2x-4 | | 8c+(5c-3)= | | 5b+4=2(b+2) | | 9k-19-8k=-2k+11 | | 143+2x=-10x+1 | | 12y+2(13y+4)=122 | | v+7=3v-3 | | 0.67+0.13t=2.49t-1.10 | | 2m-1+4m=-13 | | -13=5-13+3a | | 25s^4-9p^2=0 | | 5x-3(x-3)=-6-4x+7 |